Dynamics of changes in the ultrastructural characteristics of the mucosa and cartilage of the larynx of rats at the end of 35 and 42 days of experimental opioid exposure and after 56 days with opioid withdrawal - K. Ivasivka; E. Paltov; Z. Masna; I. Chelpanova (Kazimierz Wielki University, 2021)
In our work, we studied the ultrastructural organization of rat laryngeal mucosa and cartilage at the end of 35 and 42 days of experimental opioid exposure and at the end of 56 days with opioid withdrawal. As a result of our study at the end of the 35th day at the ultrastructural level revealed hypersecretion of goblet cells, mucus contained impurities of lymphocytes, single neutrophils and erythrocytes. In the enlarged lumens of the hemocapillaries of the lamina propria of the mucous membrane and submucosal base of different parts of the larynx, the adhesion of erythrocytes was noted. At the end of 42 days in rats, the changes were characterized by moderate damage to cytoplasmic organelles in epitheliocytes. Alternative changes developed in the chondrocytes of elastic and hyaline cartilages. Marked by an increase in the number of active fibroblasts, next to which were numerous fibrils of collagen fibers. The main substance of connective tissue, near dilated vessels, was impregnated with transudate, which was accompanied by the development of perivasal edema. Glycogen grains and vacuoles filled with neutral fats were visualized in the cytoplasm of chondrocytes.At the end of 56 days in rats with two-week withdrawal of the opioid analgesic, we found the development of alternative processes in the epitheliocytes of different parts of the larynx, as well as in chondrocytes, especially in elastic cartilage. Dyscirculatory processes in vessels of own plate of a mucous membrane and a submucous basis of various departments of a larynx were registered. Necrotic changes developed in the columnar epitheliocytes of the submucosal mucosa. Mitochondria swelled, their matrix brightened, cristae collapsed. The results of the article correspond to the research plan of  Danylo Halytskyi Lviv National Medical University and are part of the research topic of the Department of Normal Anatomy "Morphofunctional features of organs in pre - and postnatal periods of ontogenesis, under the influence of opioids, food supplements, reconstructive surgery and obesity" 0120U002129) during 2020 - 2024.